Evaluation of hematopoietic cells and myeloid/erythroid ratio in the bone marrow of the pheasant (Phasianus colchicus) - Mina Tadjalli; Saeed Nazifi; Rahil Haghjoo (Veterinary Research Forum, 2013)
In order to study the normal hematopoiesis, cellular components and myeloid/erythroid (M/E) ratio in the bone marrow of the pheasant (Phasianus colchicus), bone marrow samples were collected from the proximal tibiotarsus bone of 16 clinically healthy adult pheasant. The bone marrow smears were stained using the Giemsa stain. The results indicated that the development and formation of blood cells in the bone marrow of pheasant were similar to other birds, whereas the morphology of the cells was similar to chickens, ducks, quail, and black-head gull. The mean M/E ratio was 1.24, the mean erythroid percentage was 42.24, the mean myeloid percentage was 52.62, and the mean percentage of all other cells percentage was 5.38. There was no significant difference in any of the cellular composition between male and female.